1994
DOI: 10.1088/0953-8984/6/46/034
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure and chemical stability of the AlB2-type transition-metal diborides

Abstract: The electronic structures of the AlB2-type transition-metal diborides TMB2 (TM=Sc,Ti,V,Cr,Mn,Y,Zr,Nb,Mo,Hf,Ta) have been calculated by using the self-consistent LMTO-ASA method. The binding mechanism is discussed and the rigid-band model is shown to provide a fairly good description of their electronic structures. The existence of a pseudogap in the total density of states is found to be a common feature of these compounds. The variation of the chemical stabilities of these diborides is analysed and we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…4, and it is in a qualitative agreement with the results of KKR-ASA [7] and LMTO-ASA [8][9][10] In order to evaluate the bulk modulus value to be used in the analysis of the pressure effects in CrB 2 , the band structure calculations were performed for a number of lattice parameters close to the experimental ones (the ratio c/a was fixed at its experimental value 1.033). The equilibrium unit cell volume V th and the corresponding theoretical bulk modulus B LDA were determined from the calculated volume dependence of the total energy E V ( ) by using the well known Murnaghan equation [14], and appear to be V th = 21.79 C 3 and B LDA = 3.23 Mbar.…”
Section: Band Structure Calculationssupporting
confidence: 55%
See 1 more Smart Citation
“…4, and it is in a qualitative agreement with the results of KKR-ASA [7] and LMTO-ASA [8][9][10] In order to evaluate the bulk modulus value to be used in the analysis of the pressure effects in CrB 2 , the band structure calculations were performed for a number of lattice parameters close to the experimental ones (the ratio c/a was fixed at its experimental value 1.033). The equilibrium unit cell volume V th and the corresponding theoretical bulk modulus B LDA were determined from the calculated volume dependence of the total energy E V ( ) by using the well known Murnaghan equation [14], and appear to be V th = 21.79 C 3 and B LDA = 3.23 Mbar.…”
Section: Band Structure Calculationssupporting
confidence: 55%
“…The electronic spin susceptibility of CrB 2 is also an order of magnitude higher than that of other diborides, demonstrating a large exchange-enhancement effect. The band structure calculations for CrB 2 [7][8][9][10] have shown that its Fermi level lies in a region of the high density of electronic states (DOS). Therefore the Stoner criterion is nearly fulfilled in CrB 2 , and the susceptibility enhancement factor, S ; 9, was estimated [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that the B-B bond length in the diborides ranges from 1.7 to 1.8A˚, values typical of B-B single bonds, immediately suggests that there is an insignificant degree of p bonding between the B atoms. This conclusion is supported by recent electronic structure calculations and other data indicating that the metal-boron bonding is largely covalent in nature [8][9]. Although the structures of the diborides are unique, their physical properties are somewhat similar to those of nitrides and carbides; they are extremely hard and have very high melting points [10].…”
Section: Introductionsupporting
confidence: 58%
“…In addition, the F ( ) p N E values in the fourth group (TiB 2 , ZrB 2 , and HfB 2 ) are consistently smaller than those in the fifth group (VB 2 , NbB 2 , and TaB 2 ). This observation agrees with the picture within a rigid-band scenario: F E falls at the DOS minimum for TM = Ti, Zr, Hf, and shifts to Table. compound higher DOS with increasing d-electron counts [22,23,31]. Therefore, the present NMR investigation gives an experimental understanding for the electronic band characteristics of these diborides.…”
Section: Analysis and Dissussionmentioning
confidence: 74%